Innovative treatment formats, technologies, and clinician trainings that improve access to behavioral pain treatment for youth and adults - Darnall, Beth D.; Edwards, Karlyn A.; Courtney, Rena E.; Ziadni, Maisa S.; Simons, Laura E.; Harrison, Lauren E. (Frontiers in Pain Research, 2023)
Chronic pain is prevalent across the lifespan and associated with significant individual and societal costs. Behavioral interventions are recommended as the goldstandard, evidence-based interventions for chronic pain, but barriers such as lack of pain-trained clinicians, poor insurance coverage, and high treatment burden, limit patients' ability to access evidenced-based pain education and treatment resources. Recent advances in technology offer new opportunities to leverage innovative digital formats to overcome these barriers and dramatically increase access to high-quality, evidenced based pain treatments to youth and adults. This scoping review highlights new advances. First we describe system level barriers to broad dissemination of behavioral pain treatment. Next, we review several promising new pediatric and adult pain education and treatment technology innovations to improve access and scalability of evidence-based behavioral pain treatments. Current challenges and future research and clinical recommendations are offered.